MiSCi: Autonomic reflective middleware for smart cities - Aguilar Castro, J. (2016)
Context analysis in intelligent environments allows making the services and information available to support the activities of individuals ubiquitously. Under this premise we define smart cities, which are intelligent large-scale environments, with large amounts of data that are used to improve the quality of life for its citizens. The smart cities support activities to improve traffic, health, government, sociability, among others. This proposal seeks to create a middleware for Smart Cities from the vision of intelligent environments modeled as intelligent agents that can be adapted to the existing dynamism in a city, using emerging ontologies that not only adapt to the context of the moment and in real time, but respond unforeseen situations (emerging). Similarly, the middleware should allow scalability of the environment, to maintain the performance both in small big towns. © Springer International Publishing AG 2016.